PERAN GURU DALAM MEMOTIVASI BELAJAR SISWA KELAS X PADA MATA PELAJARAN AL-QUR’AN HADITS DI MADRASAH ALIYAH UNGGULAN AMANATUL UMMAH PACET MOJOKERTO - Nila Nur Pratiwi; Muhammad Hanief; Moh Eko Nasrulloh (VICRATINA, 2022)
This study aims to determine how students' learning motivation, the teacher’s role in motivating student learning and the inhibiting factors of teachers in motivating class X student learning in Al-Qur’an Hadith subjects at MAU Amanatul Ummah Pacet Mojokerto. Data collection techniques are observation, interviews, and documentation. Observation is used to the research location to see directly the object of research regarding matters that have to do with the problem being studied while learning is in process. This study uses an interview technique that is direct question and answer to respondents to obtain the necessary data, namely with the deputy coordinator of the MAU Amanatul Ummah, teachers and class X students. The object of this research is the teacher’s role in motivating the learning off class X student in the subject of Al-Qur’an Hadith at MAU Amanatul Ummah Pacet Mojokerto. The data processing techniques are data collection techniques in the form of written interview guidelines, etc. as well as data analysis techniques using qualitative descriptive methods. Based on the results of the study, it can be concluded that the teacher’s role in motivating the learning of class X students in the Al-Qur’an Hadith subject at MAU Amanatul Ummah Pacet Mojokerto has been carried out well and has a very important role. While the obstacles experienced by Al-Qur’an Hadith teachers are various levels of understanding, weakness, and student fatigue.